Geology, geochemistry, geophysics, mineral occurrences, and mineral resource assessment for the commonwealth of Puerto Rico editor, Walter J. Bawiec ; in cooperation with Puerto Rico Department of Natural Resources, University of Puerto Rico at Mayagüez. [electronic resource] (2001)
Summary goes here